Uruguay 2014: Not much of a change in a changing country. (June 2015) - Altman, David; Buquet, Daniel
Highlights: Political background. Electoral system. Internal elections (Partisan authorities and party primaries). The campaign for the October's election. The election of October and the runoff of November.